Prophet’s glorification in the Holy Qur’an (objective study) (Journal of the College of Basic Education, 2022)
Qur’anic glorification is the worship that God Almighty commanded His servants to practice at all times, because by means of which God saves His servants from the most difficult circumstances and situations and through which they ascend to the levels of human perfection, and the best remembrances are what God has chosen for His servants. It was specific to the glorification of angels, and some of it was specific to the glorification of the believers, and some of it was specific to the glorification of trees, thunder and mountains, and some of it was specific to the glorification of his prophets. God and his praise are among the creatures, and we will try in our research to stand on what was mentioned in the Book of God Almighty from the verses in which the glorification of the Prophet, may God’s prayers and peace be upon him and his family, was mentioned.